2017
DOI: 10.1037/pro0000153
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to mobile application use during PTSD treatment: Clinician adoption of PE coach.

Abstract: Public Significance StatementThis article suggests that several factors facilitate or serve as barriers to the use of features of PE Coach, a treatment companion mobile application used during prolonged exposure. Adoption of PE Coach may be improved by leveraging facilitators and mitigating the impact of barriers. Some lessons learned may have relevance to the adoption of other behavioral health technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 17 publications
1
33
0
Order By: Relevance
“…Indeed, even when people do use existing mental health apps, they typically only use 1 or 2 features. For example, in an evaluation of PE Coach, which contains a number of features, it was found that clinicians and patients mostly used the app to audio-record sessions [16]. This gap between the design of mental health apps, which is typically based on complex psychotherapy models, and how people use their devices, which commonly occurs in short bursts for single purposes, likely is 1 reason for the low engagement with mental health apps seen in real-world settings [17].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, even when people do use existing mental health apps, they typically only use 1 or 2 features. For example, in an evaluation of PE Coach, which contains a number of features, it was found that clinicians and patients mostly used the app to audio-record sessions [16]. This gap between the design of mental health apps, which is typically based on complex psychotherapy models, and how people use their devices, which commonly occurs in short bursts for single purposes, likely is 1 reason for the low engagement with mental health apps seen in real-world settings [17].…”
Section: Introductionmentioning
confidence: 99%
“…Establishing the standards for creating PTSD-related mHealth apps and following them seem to be essential in transferring mobile apps to the clinical field [ 4 ]. Moreover, practitioners need to explore the factors facilitating and limiting the effective use of mHealth for PTSD treatment [ 57 , 58 ]. Cooperation between mobile app creators, researchers, and practitioners is essential in creating new technology that will match the needs and expectations of both health care staff and patients [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar research has been conducted among VA CBT-i providers yielding comparable findings for CBT-i Coach (48,49). Finally, a qualitative study of 25 VA PE providers (who reported using PE Coach with 450 of their patients) found that providers appreciated that the app enhanced treatment credibility, "side-by-side" collaboration, and having forms and resources consolidated in the app, but did not appreciate lack of parity between Android and iOS versions of the app and not being able to readily access data stored in the app (60).…”
Section: Cbt-i Coachmentioning
confidence: 92%